When to Be What? Why Science-Inspired Naturalism Need Not Imply Religious Naturalism - Drees, Willem B. (Zygon, 2021)
In The Aristos, John Fowles imagined the human situation as that of a diverse group of people on a raft, apparently between a wreck in the past and a shore where they will land. But there was no wreck, there is no shore. The conference on which this thematic set of papers draws was about a similar multitude of perspectives. Some identify as religious naturalists, others as naturalists without religion, while others respect science but identify with a historic tradition. In this contribution, I defend the intellectual and moral value of science-inspired naturalism. But I also offer a variety of reasons why naturalism may not be all. In philosophical anthropology and in life, whether religious or nonreligious, dualistic and pluralist perspectives are appropriate, while one may be agnostic on ultimate questions.